2013
DOI: 10.22401/jnus.16.4.21
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Some Inflammatory Proteins and Autoantibodies in Diabetic Type II Patients

Abstract: Diabetes mellitus type II considers as inflammatory disease, which it associated with increasing level of sensitive inflammatory proteins, Adult patients with DM type II may progress a slowly failure of Beta-cells. Some patients show an autoimmune nature of the disease, our Present study aimed toevaluatethe relationship between autoantibodies which includes islet cell antibodies and insulin autoantibodies along with some inflammatory sensitive proteins like Ceruleplasminand Transferrinin type II diabetes melli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Genetic polymorphism of P-selectin gene was investigated at the position -2123C/G, that corresponded to two alleles (G and C), which was presented with three genotypes (GG, GC and CC) in DMT2 patients and healthy control figure (1).The results showed that genotypes frequencies in control group was in a good agreement with Hardy-Weinberg equilibrium(HWE), no significant differences between the observed and expected frequencies in healthy Control, while a significant differences between the observed and expected frequencies in Patients with DMT2 that deviation from HWE may be because the small size of sample and blood relation Table (3).…”
Section: S = Significant Differences (P<005)* Ns= Non Significantmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic polymorphism of P-selectin gene was investigated at the position -2123C/G, that corresponded to two alleles (G and C), which was presented with three genotypes (GG, GC and CC) in DMT2 patients and healthy control figure (1).The results showed that genotypes frequencies in control group was in a good agreement with Hardy-Weinberg equilibrium(HWE), no significant differences between the observed and expected frequencies in healthy Control, while a significant differences between the observed and expected frequencies in Patients with DMT2 that deviation from HWE may be because the small size of sample and blood relation Table (3).…”
Section: S = Significant Differences (P<005)* Ns= Non Significantmentioning
confidence: 99%
“…Diabetes is a major public health problem because it is world's sixth cause of death. An inflammatory disease that associated with many inflammatory markers, which is a key for complications of vascular endothelial system, literally for high risk populations [1]. The disturbance of endothelial factors and circulating levels of adhesion molecules which are elevated in the sera of patients.…”
Section: Introductionmentioning
confidence: 99%